Evolving landscape of hepatitis C research in the Eastern Mediterranean Region: A comprehensive bibliometric analysis from 2004 to 2024 - Kamiar Izadpanah; Seyed Aria Nejadghaderi; Hamid Sharifi (Journal of Health, Population and Nutrition)
Abstract Background Hepatitis C presents a significant public health challenge in the Eastern Mediterranean Region (EMR), which has the highest global disease burden. This study aims to provide a comprehensive overview of Hepatitis C-related research in the EMR using bibliometric analysis. Methods Between January 1, 2004, and December 31, 2024, a bibliometric search was conducted using the Scopus database to identify Hepatitis C-related publications from countries in the EMR. The analysis was performed using the R-based Bibliometrix tool, which examined research productivity trends, recent themes, thematic evolution, and co-occurrence networks of terms. Results The analysis identified 9,357 publications with an 8.06% annual growth rate and 170,021 total citations. Two distinct research clusters emerged: treatment regimens and epidemiological studies. Thematic evolution revealed a consistent focus on cirrhosis and hepatocellular carcinoma, while treatment approaches shifted from interferon-based therapies to direct-acting antivirals. Analysis of genotype-related research highlighted the regional importance of Genotype 4. Recent trends indicated integrating Hepatitis C research with broader public health concerns like COVID-19. Conclusions The Hepatitis C research landscape in the EMR is dynamic and maturing, characterized by substantial growth, diversification of research themes, and adoption of advanced treatment strategies. The findings underscore the need for continued multidisciplinary efforts and a focus on emerging themes to advance Hepatitis C management further and improve regional patient outcomes.